The Effect of Customer Experience and Perceived Enjoyment on Revisit Intention at 818 Billiard X Nati Coffee Palu - Isra Mawarni Tahir Stella; Santi, Ira Nuriya; Rombe, Elimawaty; Fitrisam, Syarifah Aliyah (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the inconsistent effects of Customer Experience and Perceived Enjoyment on Revisit Intention at 818 Billiard X Nati Coffee. It aims to analyze the partial and simultaneous effects of both variables. An explanatory quantitative design was applied using purposive sampling, a Likert-scale questionnaire, and multiple linear regression with 90 respondents. The results show that Customer Experience has no significant effect, whereas Perceived Enjoyment has a positive and significant effect; jointly, both variables are significant, with an R² of 65.6%. The findings imply that management should prioritize enjoyment, comfort, entertainment, and facility quality to encourage repeat visits.